2015
DOI: 10.1111/obr.12304
|View full text |Cite|
|
Sign up to set email alerts
|

The association between quitting smoking and weight gain: a systemic review and meta‐analysis of prospective cohort studies

Abstract: This systematic review and meta-analysis aimed to quantify weight gain after smoking cessation and the difference in weight gain between quitters and continuing smokers. Five electronic databases were searched before January 2015. Population-based prospective cohort studies were included if they recorded the weight change of adult smokers from baseline (before smoking cessation) to follow-up (at least 3 months after cessation). Thirty-five cohort studies were identified, including 63,403 quitters and 388,432 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(92 citation statements)
references
References 115 publications
(163 reference statements)
10
71
3
2
Order By: Relevance
“…Special considerations should include assessment of level of nicotine dependence, which is associated with difficulty in quitting and relapse (149). Although some patients may gain weight in the period shortly after smoking cessation (150), recent research has demonstrated that this weight gain does not diminish the substantial CVD benefit realized from smoking cessation (151). One study in smokers with newly diagnosed type 2 diabetes found that smoking cessation was associated with amelioration of metabolic parameters and reduced blood pressure and albuminuria at 1 year (152).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Special considerations should include assessment of level of nicotine dependence, which is associated with difficulty in quitting and relapse (149). Although some patients may gain weight in the period shortly after smoking cessation (150), recent research has demonstrated that this weight gain does not diminish the substantial CVD benefit realized from smoking cessation (151). One study in smokers with newly diagnosed type 2 diabetes found that smoking cessation was associated with amelioration of metabolic parameters and reduced blood pressure and albuminuria at 1 year (152).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Several studies have reported an increase in weight after smoking cessation [119,120]. A prospective study Inter99 (1-year follow-up) investigated changes in WC after smoking cessation.…”
Section: Smokingmentioning
confidence: 99%
“…Tian ve ark. [38] ise sigarayı bırakanların vücut ağırlığında artış olduğunu belirtmişlerdir. Türkiye'de hafif şişmanlık ve obezite prevalansını irdeleyen bir derlemede de sigara bırakmanın obezite ile ilişkili risk faktörleri arasında yer aldığı vurgulanmıştır [7].…”
Section: Discussionunclassified